Fine-grained data integrity check for power cloud computing - Yang, Yun; Wu, Lie; Yan, Yulin; Xu, Cong (2012 5th International Conference on Biomedical Engineering and Informatics, 2012)
With the expansion and complexity of power system, power cloud computing meets the needs of power system, which is better in data storage, data processing and control technologies and strategies. And security issue is considered as an important part and is highly regarded. In this paper, according to the security model of cloud computing, we focus on studying the data integrity of massive storage system in the power cloud computing, and a fine-grained data integrity check based on combination is proposed. The method compresses effectively the check value for data integrity to reduce storage, and improves the check efficiency of multi-error data objects.